تقويم الاختبارات الموضوعية في كلية التمريض- جامعة تشرين للعام الدراسي 2014-2015 (دراسة وصفية) - طويل علاء (Latakia University Journal -Medical Sciences Series, 2017)
الأسئلة الامتحانية (الاختبارات) لها دور مهم في تقويم مخرجات تعلم الطلبة، وتقدير مستوى تحقيقهم للأهداف المنشودة؛ لذا تعد مهارة صياغة الأسئلة الامتحانية أحد أهم المعايير التي ينبغي أن تكون ضمن معايير جودة التقويم. تعتبر الاختبارات الموضوعية أحد أنواع الاختبارات التي تقدم للطالب عدة إجابات للسؤال الواحد أو حلول للمشكلة، وعليه أن يختار (يحدد) الإجابة أو الحل المناسب لهذه الأسئلة، وتسمى بالموضوعية تصحح بالطريقة الموضوعية، بمعنى آخر؛ لا يختلف تصحيحها من مصحّح لآخر. نظراً لأهمية صياغة هذا النوع من الأسئلة وندرة الأبحاث التي تناولت هذه الفكرة فقد، هدف هذا البحث إلى تقويم مدى تحقيق الاختبارات الموضوعية لشروط صياغة الاختبارات الموضوعية، و تمثلت عينة البحث بكافة النماذج الامتحانية الكتابية النهائية (الفصل الثاني) المتعلقة بالمواد التي تُدرّس من قبل أعضاء الهيئة التدريسية في كلية التمريض للسنوات الأكاديمية الأربعة للعام الدراسي 2014-2015, وتكونت من 719 سؤال اختبار متعدد الخيارات، و248 عبارة صح- خطأ، و 21 عبارة تناسب. وكان من أبرز نتائج البحث: اتباع أعضاء الهيئة التدريسية لشروط صياغة المتن في الأسئلة المتعددة الاختيارات مع الحاجة إلى الإنتباه إلى الوضوح والدقة اللغوية، واتباع الشروط في صياغة البدائل في الاختبار المتعدد الخيارات، واتباع جميع شروط صياغة الاختبار من نوع الصح- خطأ، مع الاعتماد بشكل كبير على نوعي الاختبار المتعدد الخيارات و صح- خطأ، في حين كان الاعتماد على الاختبار من نوع التناسب (المزاوجة) قليل جداً. Exam )objective tests) have an important role in the evaluation of student’s intended learning outcomes, and estimates the level of their meeting of the sought goals. Therefore, the skill of formulating exam tests is one of the main criteria that should be within criteria of the evaluation quality. An objective test is one of the sorts that offers a student with a number of answers to a question or solutions to a problem, and then the student should identify (recognize) the right answer or solution to these questions. They are called "Objective Tests" because they are objectively corrected, in other meaning, its correction doesn’t differ from one evaluator to another. Because the importance of formulating this type of questions and scarcity of researches concerned this idea. This research aimed to evaluate the achievement of the formulated objective tests for formulated objective test conditions. The taken research sample was the final written exam (second term) which represented the courses of the four years that are taught by faculty staff members at Nursing Faculty for the academic year 2014 -2015. The sample was consisted of 719 multiple-choice question, 248 True/False item, and 21 Match item. The most significant findings were: the faculty members followed the conditions of formulating stem in multiple-choice questions with the need to pay attention to language clarity and accuracy. In addition, they followed the conditions in formulating alternatives in multiple-choice tests, and follow all test-type formulation conditions for True/False items, with relying heavily on multiple-choice questions and True/False items, while relying on the test of match items (proportionality) type was very few.